Factors Influencing the Adoption of Broadband Mobile Internet in Learning Organization: A Case of Postgraduate Students of UUM Kuala Lumpur - Zaida, Zainuddin (2012)
The Internet Broadband is supposed to have significant impact to organizations because they think that the Internet will create special value to their business. The business value of the Internet Broadband comes from the ability to derive strategic organization value from the Internet while at the same time, an organization have an obligation to disseminate information globally, communicate with various parties, and doing trade interactively with customized information and services for individual customers. The general purpose of this study was to find out whether a relationship between factors adoption of Broadband Mobile Internet (BMI), person characteristics and ICT characteristics of users. This study was conducted among the postgraduate student in Universiti Utara Malaysia (Kuala Lumpur Branch) where the study setting and sample selection will be determined by the convenience sampling method. Major findings shows that the significant positive relationships between factors adoption of Broadband Mobile Internet (BMI), person characteristics and ICT characteristics offer a clear indication of the importance of features to explain consumer acceptance behavior. The result of correlation, linear regression and multiple regressions in assessing the variables or the empirical relationship between person characteristics and ICT characteristics contribute were positively related to adoption as hypothesized. The positive association among all independent variables to dependent variable was supported. At the end, this study will recommend some idea on how to increases the quality of broadband usage with specific to university students in Malaysia.